A Multi-Residue Analytical Method for Assessing the Effects of Stacking Treatment on Antimicrobial and Coccidiostat Degradation in Broiler Litter - Solomon Efriem; Malka Britzi; Stefan Soback; Chris Sabastian; Sameer J. Mabjeesh (MDPI AG, 2024)
Antimicrobial drugs and coccidiostat compounds are commonly used in poultry farming. These compounds are subsequently excreted and released into the environment via broiler litter (BL) and can re-enter the food chain as fertilizer or animal feed. Such residue in animal feed can encourage the appearance of antibiotic-resistant bacteria as well as toxicity. Most analytical methods used to identify and quantitate these drug residues are traditional, and are specific to some antimicrobials and present limitations in assessing complex matrixes like BL. The aim of this study was to develop a multi-residue analytic method for assessing 30 antimicrobial drugs and coccidiostats associated with BL. We investigated the presence and the effects of biotic stack treatment on the degradation of drug residue in BL. Liquid-liquid extraction (LLE) and solid phase extraction (SPE) were replaced by Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) clean-up steps and detected by liquid chromatography mass spectrometry (LC/MS/MS). Results show that a wide spectrum of residues were detected from 0.4 to 8.9 mg kg−1. Following lab-scale stacking treatment, tilmicosin and eight coccidiostats persisted in BL (26-100%). This research supports the need for better understanding, regulation, and management of the use of BL that might carry a high risk of residue drugs.